Maternal serum βhCG level and uterine artery doppler studies as predictors of pregnancy induced hypertension and intra uterine growth restriction: a prospective study - Sheth, Vishal S.; Nakum, Kanaklata D.; Patel, Mehul D.; Lunagariya, Mayank R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: PIH, a pregnancy-specific disorder, is one of the major causes of maternal and perinatal morbidity and mortality worldwide.PIH and fetal growth restriction are important causes of perinatal and maternal morbidity and mortility. Methods: Hundred Indian pregnant women in their second trimester (13-20 weeks) and in their late second trimester (24-28 weeks) investigated for their serum β-hCG level and uterine artery Doppler studies respectively, attending OPD/IPD in Sir T. hospital, Bhavnagar from June 2014 to June 2015. Results: There is no clinical significance between parity and occurrence of PIH (p=0.2) and FGR (p=0.7). Out of 77 patients with their β hCG level ≤2 MoM, 2 patients (2.59%) developed PIH and FGR. And from 12 patients with their β hCG level ≥2 MoM 10 patients (80%) developed PIH and FGR which is highly significant (p<0.001). The study establishes the validity of beta HCG as a predictor of PIH and FGR with the sensitivity of 83.3%, specificity of 97.5%. Conclusions: This study can be concluded by there is a strong association between high maternal serum ß-hCG level, abnormal uterine Doppler studies with predicting adverse outcome of pregnancy like PIH and FGR. There is also a good association between high maternal serum ß-hCG level and rising severity of the disease.